The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s10396-023-01289-9
|View full text |Cite|
|
Sign up to set email alerts
|

Contrast analysis in ultrafast ultrasound blood flow imaging of jugular vein

Abstract: Purpose The contrasts of flowing blood in in vitro experiments using porcine blood and in vivo measurements of human jugular veins were analyzed to demonstrate that the hemorheological property was dependent on the shear rate. Methods Blood samples (45% hematocrit) suspended in saline or plasma were compared with examine the difference in viscoelasticity. Ultrafast plane-wave imaging at an ultrasonic center frequency of 7.5 MHz was performed on dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The result of the conventional contrast method 16) was compared to that with deep learning model. The flow of the conventional contrast method is shown in Fig.…”
Section: Conventional Contrast Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The result of the conventional contrast method 16) was compared to that with deep learning model. The flow of the conventional contrast method is shown in Fig.…”
Section: Conventional Contrast Methodsmentioning
confidence: 99%
“…Our previous study has reported that a higher flow rate (high flow velocity) induces a higher rate of presence of nonspeckle regions in in vitro experiment using porcine blood. 16) Since the main component in blood is RBC, the detection of non-speckle regions may lead to the evaluation of blood properties such as viscoelasticity dependence, morphology, and acoustic impedance contrast between RBCs and plasma or other cells such as white blood cells and platelets. Also, in our previous study, the contrasts between vessel lumen and surrounding tissues have been analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Techniques for measuring cardiovascular function using ultrasound have been extensively studied [1][2][3] and assessment of the mechanical properties of compositions in a carotid arterial wall is useful for the diagnosis of atherosclerosis. The stiffness of a carotid arterial wall is evaluated by pulse wave velocity [4][5][6] and stiffness parameter β 7,8) with ultrasound in clinical situations.…”
Section: Introductionmentioning
confidence: 99%